THEMATIC VIDEO STIMULATES STUDENT IMAGINATION FOR POETRY WRITING COURSE - Ariani, Dewi; Majid, Faizah Abdul (Jurusan Sastra Indonesia, 2024)
nnovation in the field of learning is needed so that learning becomes interesting and fun. The development of learning innovations in the form of thematic videos stimulating students' imagination to write poetry is one of the efforts to make learning to write poetry fun and make it easy to write poetry. The method used to develop thematic videos stimulating students' imagination to write poetry is the ADDIE method. Imagination-stimulating thematic videos cover four broad themes: nature, events, self-portraits, and fiction. Each theme consists of five videos with a duration of 5 minutes so the total videos produced are 20 videos. Imagination-stimulating thematic videos are accompanied by guidebooks and even complete with course descriptions, semester learning plans, and lecture units of the first to sixteenth meetings. Video thematic imagination stimulants proved to be able to arouse the imagination of students before writing poetry, in fact when the video I tested in a poetry writing class in 2018, they were so absorbed that even some students were moved and cried when watching the imagination-stimulating video of the self-portrait theme, namely 'mother'. The results of the trial showed that thematic videos stimulating imagination were able to provoke students to be more productive in writing poetry.